Expressive Utterances in Online Guest Reviews in Merumatta Senggigi-Lombok Hotel: A Pragmatic Analysis - Jessica Herly; Agus Syahid; Abdul Muhid; Syamsurrijal Syamsurrijal; Lela Rahmawati (Humanitatis : Journal of Language and Literature, 2026)
This study examines expressive utterances in guest reviews to identify their types and the linguistic markers that realize them. In the digital era, online guest reviews have become an influential form of electronic word-of-mouth that shapes public perceptions of hotel service quality. These reviews frequently contain expressive utterances that reveal guests’ emotional evaluations of their experiences. This study aims to identify the types of expressive utterances and examine the linguistic markers and politeness strategies used in online guest reviews of Merumatta Senggigi–Lombok Hotel. Employing a qualitative descriptive method, the data were drawn from 28 purposively selected TripAdvisor reviews and analyzed using document analysis procedures. The analysis was guided by Speech Act Theory and Politeness Strategy Theory, following the stages of data reduction, data display, and conclusion drawing. The findings reveal ten types of expressive utterances, namely praise, appreciation, compliment, gratitude, complaint, criticism, regret, blame, anxiety, and negative recommendation, with compliments, appreciation, and complaints occurring most frequently. Positive expressive utterances are primarily realized through evaluative adjectives and intensifiers, while negative utterances tend to employ negation, contrastive structures, hedging, and narrative framing to mitigate face-threatening acts. These results demonstrate that expressive utterances in online hotel reviews function not only as emotional expressions but also as pragmatic strategies shaped by politeness considerations in digital communication.